Evaluating the Efficacy of ChatGPT for Grammar Assessment and Personalized Feedback - Nur Aeni; Muhammad Tahir; Andi Sahtiani Jahrir (Journal of English Culture, Language, Literature and Education, 2025)
This research investigates the role of the AI chatbot ChatGPT in grammar assessment and personalized feedback for second grade students at SMKN 10 Makassar It aims to evaluate ChatGPT s accuracy in assessing students grammatical competence the effectiveness of its feedback in enhancing grammar skills and students perceptions of its usefulness as a grammar learning tool Using a mixed method explanatory sequential design quantitative data were collected through a structured questionnaire involving 46 students while qualitative insights were gained through interviews with six purposively selected participants The findings revealed that a majority of students perceived ChatGPT as accurate and consistent in identifying grammatical errors particularly appreciating the clarity and specificity of its feedback Furthermore the data indicated that ChatGPT contributed to improved grammar understanding and motivation especially through personalized explanations and error correction Qualitative responses supported these findings highlighting students increased confidence and engagement in grammar learning While some neutral responses suggested room for refinement in feedback fairness and bias perception the overall results demonstrate ChatGPT s potential as an effective supplementary tool in grammar instruction This research contributes to the growing literature on AI assisted language learning and offers practical implications for integrating technology into grammar teaching at the junior high school level < p>